The Influence of Facilities and Accessibility on Visitor Satisfaction at the Yamaha Fazzio Youth Festival Medan Event in 2024 - Gaol, Jesika Mayasari Lumban; Musriza, Irwan (Journal of Economics and Social Sciences (JESS), 2025)
This study, entitled “The Influence of Facilities and Accessibility on Visitor Satisfaction at the Yamaha Youth Festival Medan 2024”, is motivated by the importance of facilities, such as cleanliness, completeness, functionality, and physical condition, as well as accessibility, which includes distance, travel costs, and travel time, in shaping visitor satisfaction. The purpose of this research is to determine the effect of facilities and accessibility, both partially and simultaneously, on visitor satisfaction, based on consumer satisfaction theory which emphasizes the conformity between expectations and actual experiences. This study employed a quantitative method with a survey approach by distributing questionnaires to 100 respondents aged 17–30 years who attended the event, selected using purposive sampling. Data were analyzed using SPSS version 26 through validity, reliability, classical assumption tests, multiple linear regression, t-test, and F-test. The results indicate that facilities have a positive and significant effect on visitor satisfaction, accessibility also has a positive and significant effect, and both simultaneously have a significant effect on visitor satisfaction, as shown by Fcount > Ftable and sig < 0.05. The coefficient of determination (R²) of approximately 56% shows that visitor satisfaction can be explained by facilities and accessibility, while the remaining 44% is influenced by other factors not examined in this study. The discussion emphasizes that the better the facilities and the easier the accessibility provided by the organizers, the higher the level of visitor satisfaction, suggesting that event organizers should improve these aspects to create a positive experience and visitor loyalty for future events.